2019
DOI: 10.18632/aging.101698
|View full text |Cite
|
Sign up to set email alerts
|

MicroR-542-3p can mediate ILK and further inhibit cell proliferation, migration and invasion in osteosarcoma cells

Abstract: MiR-542-3p and its target gene integrin linked kinase (ILK) in human osteosarcoma together with the differentially expressed genes from osteosarcoma tissues was analyzed through bioinformatics analysis in this study. Real time quantitative polymerase chain reaction (qRT-PCR) and western blot showed that the miR-542-3p expression decreased while the ILK expression increased in the osteosarcoma tissues. The overexpressed miR-542-3p or silenced ILK restrained cell invasion, proliferation and migration and arreste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Since it was found that miRNAs were involved in chronic lymphocytic leukemia, more and more miRNAs were reported to be deregulated and correlated with tumorigenesis. As reported, deregulated expressions of miRNAs are associated with various cancers, including osteosarcoma, colorectal cancer, and lung cancer,810 which influence cancer initiation, maintenance, and metastatic progression by regulating the expressions of multiple target genes. Recently, some miRNAs have been identified to be deregulated in NSCLC samples compared with normal samples 9,10.…”
Section: Introductionmentioning
confidence: 84%
“…Since it was found that miRNAs were involved in chronic lymphocytic leukemia, more and more miRNAs were reported to be deregulated and correlated with tumorigenesis. As reported, deregulated expressions of miRNAs are associated with various cancers, including osteosarcoma, colorectal cancer, and lung cancer,810 which influence cancer initiation, maintenance, and metastatic progression by regulating the expressions of multiple target genes. Recently, some miRNAs have been identified to be deregulated in NSCLC samples compared with normal samples 9,10.…”
Section: Introductionmentioning
confidence: 84%
“…Surgical resection combined with adjuvant therapy is effective for osteosarcoma. With the development of treatment (including chemotherapy and surgery), the survival rate of osteosarcoma has increased to 65-75 % [9] . However, due to tumor recurrence and metastasis, the 5 y survival rate of patients is still very low.…”
Section: Resultsmentioning
confidence: 99%
“…A great deal of research validates that miR-542-3p, as a cancer-suppressive factor, is involved in regulating the progression of various tumors. For example, miR-542-3p suppresses esophageal cancer cell metastasis by suppressing OTUB1 expression (11); miR-542-3p can target ILK to repress osteosarcoma cell multiplication, migration, and invasion (12). When it comes to BC, a study reveals that miR-542-3p can target S1PR1 to repress BC cell proliferation, migration, and invasion (10).…”
Section: Discussionmentioning
confidence: 99%